I have a sense of humour, therefore I live Stefan Szuman and his psychological sketch On wit and humour - Kosno, Sara; Przeniosło, Marek (Laughter, humour, satire, 2024)
The following article analyses in detail such phenomena as Great Humour, Great Wit, joy, laugh, irony, joke and other accompanying concepts discussed by Stefan Szuman in his psychological essay O dowcipie i humorze. The reflections of the philosopher are presented against a broader background of his colourful biography. Due to the depth and multithreaded nature of the text, its content can be considered at various levels, so the interpretation presented by the authors is only one of many possible readings.